Lokalisasi Sistem Deteksi Lokasi Kendaraan pada Lahan Parkir menggunakan Metode Trilaterasi berbasis Protokol BLE - Muhammad Syarief Mirdasy; Agung Setia Budi (Jurnal Pengembangan Teknologi Informasi dan Ilmu Komputer, 2022)
The use of relative positioning systems has become popular in an era where network devices are used to find the location of objects or people, especially in environments that are not connected to the internet network. The use of the Global Positioning System (GPS) is indeed very helpful when the system environment has a connection to the internet. So as a solution to overcome this, to find the position of the object at a predetermined location, a relative positioning system can be used using the Bluetooth Low Energy (BLE) protocol by utilizing the Received Signal Strength Indicator (RSSI) from the device. In determining the location of the vehicle in the parking lot using the trilateration method by utilizing BLE beacons which are used as reference points that have been determined at certain locations on the location plan that act as anchor nodes. The device whose role is to capture RSSI data from each anchor node is the sensor node. Then the data owned by the sensor node is sent to the sink node to calculate the estimated distance and trilateration calculations to find out the coordinates of the location sought. The resulting coordinates are then grouped according to the division of the parking lot location plan. Based on the tests that have been carried out, the calculation of the trilateration method to find the location of objects in the parking lot has an average percentage error of 31% and an average computation time of 3.24 seconds.